Decision-making factors and their thresholds for total knee arthroplasty in lateral tibiofemoral osteoarthritis patients: a retrospective cohort study - Byung Sun Choi; Jung Min Kim; Hyuk-Soo Han (Knee Surgery & Related Research, 2022)
Abstract Background There has been no study examining lateral tibiofemoral (TF) osteoarthritis (OA) and objective decision-making factors affecting when patients decide to have total knee arthroplasty (TKA). The purpose of this study was to assess which factors and their thresholds cause patients with lateral TF OA to decide on TKA. Methods We conducted a retrospective cohort study and identified patients who had initially been diagnosed with isolated lateral TF OA from October 2004 to February 2021. We finally included 56 patients; patients who had chosen conservative treatment followed by in-depth interviews for the deliberation stage (n = 32), and the other patients who decided to undergo TKA for the decision-making stage (n = 24). Demographic, clinical, and radiographic characteristics were considered candidate predictive factors. Radiographic variables included the Ahlbäck grade, hip–knee–ankle (HKA) angle, joint line convergence angle (JLCA), and TF subluxation. Univariate and multivariate logistic regression analyses were performed. Results Clinically, the pain visual analog scale (VAS) score was significantly higher and the knee flexion angle was lower at the decision-making stage. Radiographic measurements showed that the Ahlbäck grade, HKA angle, JLCA, and TF subluxation measured at the center, in addition to the tibiotalar angle, differed statistically between the two stages. According to univariate analyses, two clinical characteristics and six radiographic variables on the ipsilateral side of the leg, and one radiographic variable on the contralateral side of the leg were included as factors influencing the patients’ decision to undergo TKA. After making adjustments based on multivariate analysis, the ipsilateral knee pain VAS (OR = 1.61; 95% CI = 1.14–2.28, p = 0.007) and medial TF subluxation measured at the center (OR = 1.14, 95% CI = 1.01–1.32, p = 0.072) were found to be significant factors for choosing TKA. The area under the curve (AUC) for pain VAS was 0.757 and the cutoff value was 4.5. The AUC for TF subluxation measured at the center was 0.697 and the cutoff value was −4.10% of medial TF subluxation. Conclusion Higher ipsilateral knee pain VAS and more severe medial TF subluxation measured at the center were independent factors affecting patient decisions to undergo TKA with lateral TF OA. Understanding the determining factors that may affect patient decision-making when considering TKA may be an essential aspect of evaluating the prognosis of patients with lateral TF OA. Level of evidence III.